Self-efficacy and workplace incivility: a contribute to understand burnout - Carvalho, Francisca Moreira Serra Aparício de (2019)
The complexity inherent to burnout, along with the dynamic nature of work context demands further research regarding the causes of this phenomenon. Emerging in the field of workplace aggression, incivility has proven to be harmful for both individuals and organisations. Hence, referencing the Job Demands-Resources Model, we hypothesised the connection of colleagues and customers´ incivility with the recently developed four-scale measure of burnout and the moderating effect of self-efficacy. Two studies were conducted - the first with data collected from a questionnaire with respondents from several companies (N = 225), and the second using the same method, with participants from a single public large organisation (N = 562). Study 1 revealed a positive link between workplace incivility perpetrated by colleagues and emotional exhaustion. However, the findings did not support the moderator effect of self-efficacy. In Study 2, workplace incivility perpetrated by customers and the other three dimensions of burnout (cognitive impairment, emotional impairment and mental distance) were incorporated. Both types of incivility were significantly related to all facets of burnout. Results, howbeit, did not support the moderation effect of self-efficacy in the relationship between workplace incivility perpetrated by colleagues and customers on emotional exhaustion. Workplace incivility perpetrated by colleagues with mental distance, emotional and cognitive impairment showed also to not be moderated by self-efficacy. In contrast, the impacts of workplace incivility perpetrated by customers on the three previously mentioned dimensions of burnout were found to be buffered by self-efficacy. Limitations and future research directions are discussed.